Effects of organic solvents on morphologies, photoluminescence, and photocatalytic properties of ZnO nanostructures. (25th September 2019) - Liang, Ce; He, Xian; Cai, Zhiwei; Chang, Gang; Lin, Sen; Hao, Yanan; Du, Yinxiao; Fan, Dongyu; Wang, Yonggang; Bi, Ke; Lei, Ming
Abstract : Employing organo‐metal zinc acetylacetonate (Zn(acac)2 ) as the zincic source, various zinc oxide (ZnO) products with different morphologies have been synthesised via a typical solvothermal method in different polar organic solvents. Quasi‐spherical and rod‐like structures with diverse sizes are successfully fabricated in the methanol, ethanol, 1‐propanol, isopropanol, and acetone solutions of NaOH, respectively. Moreover, their microstructures and morphologies have been investigated by X‐ray powder diffraction and electron microscopy. A possible growth mechanism has been proposed. The various morphologies of ZnO are attributed to the discrepant polarity and viscosity of organic solvents and the supersaturation levels of reactants. Furthermore, the size‐depended photoluminescence and photocatalytic properties of various structures of ZnO are also studied. It is believed that the different but regular photoelectric behaviours are resulting from the surface states and specific surface areas which are related to the exposed polarity facets as well as the size of ZnO particles.